PEMAKAIAN FLY-ASH SEBAGAI CEMENTITIOUS PADA BETON MUTU TINGGI DENGAN STEAM CURING (THE USE OF FLY-ASH AS CEMENTITIOUS ON HIGH-STRENGTH CONCRETE WITH STEAM CURING) - Erwin Rommel; Yunan Rusdianto (Media Teknik Sipil, 2012)
Erwin Rommel1 & Yunan Rusdianto2Jurusan Teknik Sipil Fakultas Teknik Universitas Muhammadiyah MalangAlamat Korespondensi :Jalan Raya Tlogomas 246 Malang 65144email : erwin67pro@yahoo.com HP 08123314432ABSTRACTThe use of fly-ash as cementitious will be made to utilize physical and chemical properties offly-ash that has a dominan of silica and good of modulus fines. The use of steam curing will be donein this study which can speed up the cycle of making concrete. This is advantageous in the productionof precast concrete and velocity field construction.The research was conducted by making concrete cube 15x15x15 cm for 80 pieces and thentested the compressive strength and absorption of concrete. Achieve the quality of concrete madewith the provision of K600 with giving the fly-ash respectively 7.5%, 15% and 30% by weight ofcement.The results of the research obtained by the use of fly-ash as much as 7.5% as a cementitiousthat was given to the steam curing will provide the initial strength of concrete reached 47% ofcompressive strength at 28 days. While the effect of giving fly-ash in concrete has not seen absorptionsignificantly when compared to concrete without fly-ash.Key word : concrete, fly-ash, steam curing